Environment, health and the challenges of urban drainage in the municipality of Presidente Epitácio, Western São Paulo, Brazil - Santos, Ricardo dos; Piroli, Edson Luís (National Journal of City Management, 2026)
Objective - Identify possible relationships between the environment, health, and problems arising from inadequate urban drainage in the municipality of Presidente Epitácio, state of São Paulo, contributing to reflection on the theme. Methodology - To conduct the research, bibliographic surveys, thematic maps, and analysis of secondary data on hospital morbidity and mortality from 1998 to 2019 were used, in addition to information on dengue and leishmaniasis, by place of residence, from 2007 to 2019, complemented by fieldwork. Originality/relevance – Floods are among the most serious disasters in Brazil, due to the high number of victims, people affected, and socioeconomic losses, aggravated by the expansion of impervious areas. Inadequate urban stormwater management intensifies these impacts and increases health risks, especially with regard to waterborne diseases. In this context, by integrating environmental analysis and health indicators at the local level, the research fills a gap still present in the literature, marked by a scarcity of studies that articulate these dimensions. Results – The results of hospital morbidity revealed that the most prevalent diseases are those of the respiratory system, which rank second in number of deaths. This pattern indicates the influence of environmental and urban conditions on the health of the population. In addition, data on dengue fever have been quite significant in recent years, especially in urban areas, with a worrying increase in cases of American tegumentary leishmaniasis and visceral leishmaniasis, reinforcing the relationship between inadequate urban drainage, water accumulation, and vector proliferation, indicating the need for improvements in the monitoring of health indicators, especially for water-related diseases. Theoretical/methodological contributions – The research contributes to strengthening the integrated approach between urban drainage, environment, and health and, methodologically, to articulating spatial analysis, epidemiological data, and fieldwork, encouraging the adoption of more sustainable and resilient urban drainage systems in the face of technical limitations and the high costs of traditional models. Social and environmental contributions – Drainage systems must be integrated into environmental planning, considering the dynamics of watersheds for more effective solutions, combined with nature-based alternatives and environmental education, which implies changes in habits and attitudes towards the environment.